Predictive Values of White Blood Cell Count in Peripheral Blood at Admission on In-Hospital Complications and 90-Day Outcomes of Patients with Aneurysmal Subarachnoid Hemorrhage: Insights from the LongTEAM Registry - Li R; Zhao Y; Chen X; Hao Q (Dove Medical Press, 2022)
Runting Li,1 Yuanli Zhao,1- 4 Xiaolin Chen,1,3,4 Qiang Hao1 1Department of Neurosurgery, Beijing Tiantan Hospital, Capital Medical University, Beijing, People's Republic of China; 2China National Clinical Research Center for Neurological Diseases, Beijing, People's Republic of China; 3Stroke Center, Beijing Institute for Brain Disorders, Beijing, People's Republic of China; 4Beijing Key Laboratory of Translational Medicine for Cerebrovascular Disease, Beijing, People's Republic of ChinaCorrespondence: Qiang Hao; Xiaolin Chen, Department of Neurosurgery, Beijing Tiantan Hospital, Capital Medical University, No. 119 South Fourth Ring West Road, Fengtai District, Beijing, 100070, People's Republic of China, Email haoqiang713@163.com; chenxiaolin@bjtth.orgPurpose: This study aimed to explore the relationship between white blood cells (WBCs) at admission and clinical outcomes in patients with aneurysmal subarachnoid hemorrhage (aSAH).Patients and Methods: We analyzed data from patients with aSAH between January 2015 and September 2021 who were included in the LongTEAM (Long-term Prognosis of Emergency Aneurysmal Subarachnoid Hemorrhage) registry study. WBC is classified into four groups according to the quartile. We used the logistic model for in-hospital complications, mortality, modified Rankin scale (mRS) at discharge and 90 days to examine the relationship between WBC and clinical outcomes. We used WBC levels near odds ratio (OR) = 1 (Q1) in restricted cubic splines as the reference to evaluate whether there is a nonlinear relationship between WBC and clinical outcomes. Another Kaplan-Meier method was used to analyze the relationship between WBC levels and the risk of developing pneumonia.Results: Of the 988 patients included, the results showed that compared with patients in the Q1 group, patients in the highest quartile (Q4) had an increased incidence of 90-day unfavorable outcomes after adjusting the confounders (adjusted OR = 1.81, 95% CI = 1.02- 3.20, p = 0.042), which may be caused by the increased incidence and risk of pneumonia (adjusted OR = 2.06, 95% CI = 1.30- 3.29, p = 0.002; adjusted hazard ratio [HR]=1.63, 95% CI = 1.13- 2.36, p < 0.001). The restricted cubic spline indicated that the incidence of developing pneumonia and 90-day unfavorable outcomes rises with increasing WBC levels (p for nonlinear = 0.135 and 0.113).Conclusion: Patients with higher WBC at admission were associated with an increased incidence of 90-day unfavorable outcomes, which might be related to pneumonia.Keywords: aneurysmal subarachnoid hemorrhage, white blood cell, pneumonia, functional outcome